Characterization of Maize Near-Isogenic Lines With Enhanced Flavonoid Expression to Be Used as Tools in Diet-Health Complexity - Wu, Binning; Chang, Haotian; Marini, Rich; Chopra, Surinder; Reddivari, Lavanya (Frontiers in Plant Science, 2021)
Increasing incidence of chronic diseases in the 21st century has emphasized the importance of developing crops with enhanced nutritional value. Plant-based diets are associated with reduced incidence of many chronic diseases. The growing population and increased food demand have prioritized the development of high-yielding commercial crop varieties at the expense of natural flavors as well as health-benefiting compounds including polyphenols. Flavonoids are a large subfamily of polyphenols abundant in the plant kingdom with known health-promoting effects, making them a promising trait to be re-introduced into elite lines. Given the vast array of flavonoids and the complexity of plant food metabolome interactions, it is difficult to identify with certainty the specific class(es) of flavonoids in the food matrix that are anti-inflammatory. To address this, we have developed four maize near-isogenic lines (NILs); a line that lacked both anthocyanins and phlobaphenes, a second NIL containing phlobaphenes, a third line had anthocyanins, and a fourth line that contained both anthocyanins and phlobaphenes. The phytochemical profiles and the antioxidant potential of the NILs were characterized. The accumulation of anthocyanins and phlobaphenes contributed significantly to antioxidant capacity compared to maize lines that lacked one or both of the compounds (p < 0.05). Pilot study showed that intake of flavonoid-rich maize diets were able to alleviate experimental colitis in mice. These NILs offer novel materials combining anthocyanins and phlobaphenes and can be used as powerful tools to investigate the disease-preventive effects of specific flavonoid compound in diet/feeding experiments.